I Want to (Bud) Break Free: The Potential Role of DAM and SVP-Like Genes in Regulating Dormancy Cycle in Temperate Fruit Trees - Falavigna, Vítor da Silveira; Guitton, Baptiste; Costes, Evelyne; Andrés, Fernando (Frontiers in Plant Science, 2019)
Bud dormancy is an adaptive process that allows trees to survive the hard environmental conditions that they experience during the winter of temperate climates. Dormancy is characterized by the reduction in meristematic activity and the absence of visible growth. A prolonged exposure to cold temperatures is required to allow the bud resuming growth in response to warm temperatures. In fruit tree species, the dormancy cycle is believed to be regulated by a group of genes encoding MADS-box transcription factors. These genes are called DORMANCY-ASSOCIATED MADS-BOX (DAM) and are phylogenetically related to the Arabidopsis thaliana floral regulators SHORT VEGETATIVE PHASE (SVP) and AGAMOUS-LIKE 24. The interest in DAM and other orthologs of SVP (SVP-like) genes has notably increased due to the publication of several reports suggesting their role in the control of bud dormancy in numerous fruit species, including apple, pear, peach, Japanese apricot, and kiwifruit among others. In this review, we briefly describe the physiological bases of the dormancy cycle and how it is genetically regulated, with a particular emphasis on DAM and SVP-like genes. We also provide a detailed report of the most recent advances about the transcriptional regulation of these genes by seasonal cues, epigenetics and plant hormones. From this information, we propose a tentative classification of DAM and SVP-like genes based on their seasonal pattern of expression. Furthermore, we discuss the potential biological role of DAM and SVP-like genes in bud dormancy in antagonizing the function of FLOWERING LOCUS T-like genes. Finally, we draw a global picture of the possible role of DAM and SVP-like genes in the bud dormancy cycle and propose a model that integrates these genes in a molecular network of dormancy cycle regulation in temperate fruit trees.